Tari Ringkang Jawari: Elemen Emansipasi Wanita Dalam Tari Kreasi Banten - Purwinarti, Wiwin (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2023)
Writing on Tari Ringkang Jawari: Elements of Emancipation in Banten Creative Dance aims to provide an explanation of how women's emancipation can develop and progress over time without losing their identity by revealing movement structures that have symbolic meaning and various movements and forms of presentation. Ringkang Jawari dance in the Performing Arts department as teaching material in the Banten creative dance course will be described clearly. The Ringkang Jawari dance as teaching material in the Banten Creative Dance course in the arts department has many meanings, including the symbolic meaning that exists in every dance movement, containing symbols, make-up, clothing, and accompaniment as well as meaningful and symbolic attributes. The name of the movement and meaning that is also found in the Ringkang Jawari dance is marked by the dancers who dance this dance using almadad, symbolizing the strength of Banten women in fighting for the progress of their region with a symbol of strength.Especially in the field of dance, in order to preserve and develop the Ringkang Jawari dance, which is a typical art of the Banten people, the author needs to provide wider socialization about the typical dance arts of Banten, especially the Ringkang Jawari dance, to the community by becoming learning material for courses in the performing arts department of FKIP and trying the Ringkang Jawari dance as a dance treasure in Banten.